Antecedents of Attitude Toward Counterfeit Wrist Watches - Mazhar Ali; Kashif Farhat (Pakistan Business Review, 2017)
This study aims to identify factors shaping attitude toward counterfeit products and their relative influence on attitude formation. This involves 200 potential and actual consumers of counterfeit products in an explanatory research. Antecedents of attitude toward counterfeit purchases extracted from literature review are PriceQuality Inference, Subjective Norms, Past Experience, Risk Aversion and Personal Gratification. Multiple regression and Independent Sample t-test are used to analyze the data. Results show a significant impact of past experience, risk aversion and personal gratification and insignificant impact of subjective norms and price-quality inference on attitude formation toward counterfeit wrist watches.It is recommended to use experiential marketing to convey delicate difference of experiencing original brands and enhance the perceived risk of using copied products.
Keywords: Z0; 330; Attitude; Counterfeit Products Price-Quality Inference; Subjective Norms; Information Susceptibility; Normative Susceptibility; Past Experience; Risk Aversion; Personal Gratification